Acute Pancreatitis after Colonoscopy: A Case Presentation and Literature Review - Sahil D. Doshi; Yelina Alvarez; Shria Kumar; Octavia Pickett-Blakely (Case Reports in Gastrointestinal Medicine)
We report a case of acute pancreatitis after an elective screening colonoscopy. A 51-year-old male with a left ventricular assist device for end-stage nonischemic cardiomyopathy and a family history of colorectal cancer was admitted for an expedited heart transplant evaluation. He underwent screening colonoscopy during this admission which was technically uncomplicated apart from requiring slight maneuvering at the splenic flexure. The following day, the patient developed acute epigastric pain and one episode of emesis. Subsequent laboratory evaluation revealed a significantly elevated lipase level and cross-sectional imaging consistent with acute pancreatitis. With no evidence of gallstones, alcohol use, and hypertriglyceridemia, the acute pancreatitis was deemed to be a complication of colonoscopy. The presumed mechanism of the pancreatitis was due to mechanical trauma from insufflation and abdominal pressure, applied to at the splenic flexure, which is in close proximity to the pancreatic tail. The patient was treated with supportive care (intravenous fluid, analgesia, and pancreatic rest) and improved significantly over a three-day period.